The Effect of Texapon Variations on the Quality Standards of Motor Vehicle Shampoo Derived from Residual Clothing Fragrance Production in the Industry: Vol. 13 No. 3 (2024) - Adellia Nilam Cahya; Cintiya Septa Hasannah; Meka Saima Perdani; Wilma Nurrul Adzillah (Prodi Kimia, 2024)
Laundry softener or fragrance is a liquid material that is added at the final stage of the washing process with the aim of softening and providing a fragrant aroma to clothes. The main ingredient in laundry softener is surfactant. This research aims to process leftover fragrance from one of the FMCG (Fast Moving Consumer Goods) industries in Indonesia into a motor vehicle shampoo product that has market value and can be used by the community at a more economical price, while maintaining quality comparable to commercial products. The formulation of this vehicle shampoo is determined through the trial and error method. Subsequently, samples are tested for pH, density, viscosity, foaming power, and corrosion rate. The test results obtained from this study show a pH value of 7.92, a density of 1.025 gr/cm3, a viscosity of 2.41 Pa.s, foam stability of 91.67%, and a corrosion rate of 0.0929095 mm/year, classified as